Production of Seed from Tapped and Untapped Trees in Chir Pine (Pinus roxburghii, SARG.) - Lohani, D. N.; Kureel, A. P. (Indian Forester, 1973)
The seed and cone production of tapped and untapped trees of chir pine of nine different origins growing in new forest have been studied for seed production, seed weight and germination percentage. The study shows that cone and seed production is not affected adversely by tapping, though indications are that it actually increases in trees tapped continuously for long period. The existence of twist has no effect on seed production. Tapping appears to have some effect on seed size, though the trend is not consistant. Germination percentage, however, is affected in origins which are high yielders.